The presence of coexisting sleep-disordered breathing among women with hypertensive disorders of pregnancy does not worsen perinatal outcome. - Danielle L Wilson; Mark E Howard; Alison M Fung; Fergal J O'Donoghue; Maree Barnes; Martha Lappas; Susan P Walker (PLoS ONE, 2020)
OBJECTIVE:To determine whether the presence of co-existing sleep-disordered breathing (SDB) is associated with worse perinatal outcomes among women diagnosed with a hypertensive disorder of pregnancy (HDP), compared with normotensive controls. STUDY DESIGN:Women diagnosed with HDP (gestational hypertension or preeclampsia) and BMI- and gestation-matched controls underwent polysomnography in late pregnancy to determine if they had coexisting SDB. Fetal heart rate (FHR) monitoring accompanied the sleep study, and third trimester fetal growth velocity was assessed using ultrasound. Cord blood was taken at delivery to measure key regulators of fetal growth. RESULTS:SDB was diagnosed in 52.5% of the HDP group (n = 40) and 38.1% of the control group (n = 42); p = .19. FHR decelerations were commonly observed during sleep, but the presence of SDB did not increase this risk in either the HDP or control group (HDP group-SDB = 35.3% vs. No SDB = 40.0%, p = 1.0; control group-SDB = 41.7% vs. No SDB = 25.0%, p = .44), nor did SDB affect the total number of decelerations overnight (HDP group-SDB = 2.7 ± 1.0 vs. No SDB = 2.8 ± 2.1, p = .94; control group-SDB = 2.0 ± 0.8 vs. No SDB = 2.0 ± 0.7, p = 1.0). Fetal growth restriction was the strongest predictor of fetal heart rate events during sleep (aOR 5.31 (95% CI 1.26-22.26), p = .02). The presence of SDB also did not adversely affect fetal growth; in fact among women with HDP, SDB was associated with significantly larger customised birthweight centiles (43.2% ± 38.3 vs. 16.2% ± 27.0, p = .015) and fewer growth restricted babies at birth (30% vs. 68.4%, p = .026) compared to HDP women without SDB. There was no impact of SDB on measures of fetal growth for the control group. Cord blood measures of fetal growth did not show any adverse effect among women with SDB, either in the HDP or control group. CONCLUSION:We did not find that the presence of mild SDB worsened fetal acute or longitudinal outcomes, either among women with HDP or BMI-matched normotensive controls. Unexpectedly, we found the presence of SDB conferred a better prognosis in HDP in terms of fetal growth. The fetus has considerable adaptive capacity to withstand in utero hypoxia, which may explain our mostly negative findings. In addition, SDB in this cohort was mostly mild. It may be that fetal sequelae will only be unmasked in the setting of more severe degrees of SDB and/or underlying placental disease.